Multimodal ultrasound features for distinguishing classic and aggressive subtypes of papillary thyroid carcinoma - Deng, Bixue; Zhong, Jing; Zhuang, Yu; Chen, Jiamin; Hong, Jiayi; Qin, Xiaofeng; Su, Zhongzhen; Zhang, Jiahui; Chen, Fei; Wen, Xin (Frontiers in Endocrinology, 2025)
BackgroundTo compare the sonographic features of papillary thyroid carcinoma (PTC) between classic and aggressive PTC subtypes to determine whether multimodal ultrasound (US) can aid in differentiating particular subtypes.MethodsThe retrospective cohort study included patients with histologically proven PTCs according to the World Health Organization classification of thyroid neoplasms between December 2022 and October 2024. Imaging findings were evaluated using the International Expert Consensus on US Lexicon for Thyroid Nodules. Associations between US features and intrinsic subtypes were assessed by the χ2 or Fisher’s exact test.ResultsOverall, 295 patients with 320 nodules (74 males with 81 nodules and 221 females with 239 nodules) were included. There were 279 classic PTC (87.2%), 26 tall cell (8.1%), 11 hobnail (3.4%), one columnar cell (0.3%), one solid (0.3%), and two diffuse sclerosing subtypes (0.6%). Regarding US features, direction of growth, extrathyroidal extension (ETE), calcifications, and color Doppler flow imaging significantly differed among the PTC subtypes. Tall cell subtype PTCs exhibited the highest prevalence of taller-than-wide shapes (p<0.001) and the absence of echogenic foci (p=0.047). ETE was not observed in hobnail subtype PTCs (p =0.008). The vascularity of classic and tall cell subtype PTCs usually presented as absent or rim blood signals, while the hobnail subtype commonly had vessels inside the nodule (p=0.017). All subtypes of PTC demonstrated similarly high stiffness values on SWE. The mean Emax, Emean, and Emin were 64.6 ± 38.2 kPa, 45.1 ± 29.6 kPa, and 27.7 ± 20.7 kPa, respectively.ConclusionThere were significant differences and several trends in the US characteristics of different intrinsic subtypes, providing imaging diagnostic criteria to assist in managing individuals with PTC.